Full outline of unresponsiveness scale – new powerfool tool for predicting early lethal outcome after acute ischemic supratentorial stroke? - Kozyolkin, O.; Kuznietsov, A. A.; Козьолкін, Олександр Анатолійович; Кузнєцов, Антон Анатолійович (Запорізький державний медичний університет, 2015)
Background: Identification of vital prognosis in patients with acute ischemic supratentorial stroke (AISS) using clinical parameters is a very important and relevant in modern angioneurology that can help the practicioners to improve treatment approaches. Therefore we decide to verify the clinical scale with the largest prognostic value for predicting early lethal outcome (ELO) after AISS.